2005
DOI: 10.1093/fampra/cmi068
|View full text |Cite
|
Sign up to set email alerts
|

The use of medication for chronic pain in primary care, and the potential for intervention by a practice-based pharmacist

Abstract: We have demonstrated a method of identifying patients with chronic pain in primary care, and the feasibility and acceptability of a pharmacist-led intervention. This is of potential value in primary care, as relevant prescribing recommendations were made for most patients although further research is required to assess these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…Studies reported variable implementation rates of recommendations related to DRPs, ranging from 29% [4] to 84% [26]. To our knowledge, no study has investigated the implementation of recommendations related to EPs only.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies reported variable implementation rates of recommendations related to DRPs, ranging from 29% [4] to 84% [26]. To our knowledge, no study has investigated the implementation of recommendations related to EPs only.…”
Section: Limitationsmentioning
confidence: 99%
“…However, limited and inconsistent clinical and research evidence is available to support these claims in the context of chronic pain. [11][12][13][14] A systematic review evaluating effectiveness of pharmacist-led educational interventions for chronic pain management reported a statistically significant reduction in pain intensity of 0.5 on a scale of 0 to 10, a reduction in adverse effects by 50% and an improvement in patient satisfaction with the treatment equivalent to 1 point on a 0 to 10 point rating scale in patients receiving interventions as compared to the control group. 15 To date, no systematic review has evaluated the effectiveness of pharmacist-led medication review for chronic pain management.…”
Section: Introductionmentioning
confidence: 99%
“…McDermott et al [33] published a study in 2006, one aspect of which was to assess prescribing recommendations that were made after a pharmacist-led review of analgesic prescribing and to identify the proportion of these acted on by general practitioners. A computer database was used to identify patients with chronic pain, and treatment protocols for chronic pain were agreed on at the start of the study [33].…”
mentioning
confidence: 99%
“…A computer database was used to identify patients with chronic pain, and treatment protocols for chronic pain were agreed on at the start of the study [33]. The study pharmacist reviewed the safety and efficacy of medication regimens in 132 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation